2022
DOI: 10.1002/elsa.202100163
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in ion‐sensitive field‐effect transistors for biosensing applications

Abstract: Over the past decades, considerable development and improvement can be observed in the area of the ion‐sensitive field‐effect transistor (ISFET) for biosensing applications. The mature semiconductor industry provides a solid foundation for the commercialization of the ISFET‐based sensors and extensive research has been conducted to improve the performance of ISFET, with a special research focus on the materials, device structures, and readout topologies. In this review, the basic theories and mechanisms of ISF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 142 publications
1
10
0
Order By: Relevance
“…Additionally, microfabrication techniques can be used to create microarrays of FET sensors on flexible substrates, enabling the creation of flexible, lightweight, and comfortable wearable sensors that can be integrated into clothing or attached onto skin. There are generally two types of FETs-based biosensors: organic field-effective transistor (OFET) and OECT. These two transistor-based biosensors have a similar configuration, which comprises three electrodes (i.e., source, drain, and gate electrode), a semiconducting channel layer, and a gate dielectric layer. The difference between OFET and OECT is the dielectric layer; the former one usually uses a dielectric material such as metal oxide or polymer, while the later one adopts a liquid electrolyte.…”
Section: Wearable Devices Based On Pctsmentioning
confidence: 99%
“…Additionally, microfabrication techniques can be used to create microarrays of FET sensors on flexible substrates, enabling the creation of flexible, lightweight, and comfortable wearable sensors that can be integrated into clothing or attached onto skin. There are generally two types of FETs-based biosensors: organic field-effective transistor (OFET) and OECT. These two transistor-based biosensors have a similar configuration, which comprises three electrodes (i.e., source, drain, and gate electrode), a semiconducting channel layer, and a gate dielectric layer. The difference between OFET and OECT is the dielectric layer; the former one usually uses a dielectric material such as metal oxide or polymer, while the later one adopts a liquid electrolyte.…”
Section: Wearable Devices Based On Pctsmentioning
confidence: 99%
“…Various research has also shown that the functionalization of the biomolecules at the edges of the channel surface leads to a greater change in device conductivity and sensitivity [ 14 , 16 ]. In other types of FETs, such as ISFETs and dielectrically modulated field effect transistors (DMFETs), the sensitivity hinges on the transconductance ( dI D /dV EG ) factor, which depends on the dielectric constant of the specific biomolecule [ 38 , 39 , 40 ]. Ohno et al thus demonstrated linear changes in transconductance of ISFET with adsorption of protein molecules (bovine serum albumin) at low concentrations and saturation at higher concentrations [ 38 ]; Im et al showed binding of biomolecules in DMFET that alters the dielectric constant at the gate and causes large changes in threshold voltage, which can alter the transconductance.…”
Section: Working Principle Of the Field Effect Transistor As A Biosensormentioning
confidence: 99%
“…Sensors play a crucial role in converting targeted analytes into measurable electric signals, making them a vital tool in medical care and health monitoring. [1][2][3][4][5][6][7][8] The rapid development of a large library of functionalized sensors has enabled the widespread utilization of wearable sensors over the past few decades. [9][10][11][12][13] In addition, wireless transmission technologies have evolved to achieve high-speed data transfer.…”
Section: Introductionmentioning
confidence: 99%